Three new species of calcareous nannofossil from Late Palaeocene and Early Eocene assemblages (Ocean Drilling Program Site 1262, Walvis Ridge, SE Atlantic Ocean) - AGNINI, CLAUDIA; FORNACIARI, ELIANA; RAFFI I. (Journal of Nannoplankton Research, 2008)
At Ocean Drilling Program Site 1262 (Leg 208), a composite section spanning the Lower Palaeocene to Lower Eocene was recovered from Walvis Ridge, eastern South Atlantic Ocean. Calcareous nannofossil assemblages there are moderately to well preserved. Three new species have been identified: two new species of the genus Discoaster (D. backmanii, D. paelikei) and a new species of Sphenolithus (S. rioi) are described and illustrated.